Analisa Kualitas Aplikasi Absensi Mobile Greatday untuk Mengukur Kepuasan Pengguna Mengunakan Metode Webqual 4.0: Penelitian - Imam Budiawan; Fahrizal; Martua HamiSiregar; Mushliha; Hani Harafani; Ade Setiawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The online attendance application has now become one of the systems that is starting to be widely used by companies to support ease of work in carrying out attendance activities. Starting from daily absences, permit applications, leave applications, employee overtime data to attendance recaps which can be accessed easily to present a management report. The problem that occurs is that the information service often has errors, namely the Greatday mobile application still does not receive good service or is still less responsive to users who need good attendance information services. To measure user satisfaction of the Greatday mobile attendance application, accurate and appropriate methods and measuring tools are needed, such as Webqual 4.0. Based on the test results for the coefficient of determination (R Square), the figure 0.666, the coefficient of determination is equal to 66.6%. This figure means that usability (X1), information quality (X2) and interaction quality (X3) influence consumer satisfaction (Y). Meanwhile, the remaining 100% − 66.6% = 33.4% is influenced by other variables outside the variables that were not examined.